2022
DOI: 10.5937/jomb0-31711
|View full text |Cite
|
Sign up to set email alerts
|

LX-8000R and UriSed 2 fully automated urine analyzers comparison to manual microscopic examination

Abstract: Background: Urinalysis has an important place in evaluating kidney and urinary tract infections. Automated urine analyzers enhance productivity and turnover in laboratories and economize time and labor required for analysis. In the present study, we evaluated and compared analytic and diagnostic performance of UriSed2 with LX-8000R, which is a novel image-based automated urine sediment analyzer. Methods: A total of 178 urine samples sent to our laboratory were evaluated by the two urine analyzers and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, these interventions may lead to prolonged turnaround times for urinalysis. In several studies [ 38 , 39 ], authors concluded that automated platforms performed sufficient diagnostic performance for detection of RBC, WBC, SEC, thus can replace manual microscopy. Also, in this study both systems presented same sensitivity for RBC (89.5%).…”
Section: Discussionmentioning
confidence: 99%
“…However, these interventions may lead to prolonged turnaround times for urinalysis. In several studies [ 38 , 39 ], authors concluded that automated platforms performed sufficient diagnostic performance for detection of RBC, WBC, SEC, thus can replace manual microscopy. Also, in this study both systems presented same sensitivity for RBC (89.5%).…”
Section: Discussionmentioning
confidence: 99%